The rule of the function is to multiply the input by 3, since one yard is equal in length to three feet.
So, if the input is 15.4, the output will be
![f(x)=3x \implies f(15.4)=3\cdot 15.4 = 46.2](https://tex.z-dn.net/?f=f%28x%29%3D3x%20%5Cimplies%20f%2815.4%29%3D3%5Ccdot%2015.4%20%3D%2046.2)
Answer:
answer A : (2 -5)
Step-by-step explanation:
the midipoint P,Q is the center A of this circle (because PQ is a diameter)
use : (x-6)²+(x+5)² = 16 you have : A(6 , -5) now let Q(x,y) :
(x+10)/2 = 6
(y-5)/2 = - 5
x+10 = 12
y-5 = -10
so : x = 2 and y = - 5....answer A : (2 -5)
Answer:
Answer is z= 43/36
Step-by-step explanation:
We have given,
2 13/18 - z = 1 19/36
Since 2 13/18 = 49/18 and 1 19/36 = 55/36
So we can write,
2 13/18 - z = 1 19/36
or 49/18 - z = 55/36
or 49/18 - 55/36 = z
or (98 -55)/36 = z
or 43/36 = z
Hence we got z = 43/36
Answer:
where is the spinner
Step-by-step explanation:
The phrase has two parts:
Five times the sum of a number and eleven, divided by
three times the sum of the number and eight
Let the number be x. Five times the sum of a number and eleven means 5 multiplied to the sum of x and 11. In expression this will be written as:
5(x + 11)Three times the sum of the number and eight means 3 multiplied to the sum of x and 8. In expression this will be written as:
3(x + 8)So, the overall expression will be: